2018
DOI: 10.1159/000486201
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Global DNA Methylation Is Not Exclusive to Amyotrophic Lateral Sclerosis and Is Also Observed in Spinocerebellar Ataxia Types 1 and 2

Abstract: Adult-onset neurological disorders are caused and influenced by a multitude of different factors, including epigenetic modifications. Here, using an ELISA kit selected upon careful testing, we investigated global 5-methylcytosine (5-mC) levels in sporadic and familial amyotrophic lateral sclerosis (sALS and fALS), spinocerebellar ataxia types 1 and 2 (SCA1 and SCA2), Huntington’s disease, Friedreich’s ataxia, and myotonic dystrophy type 1. We report a significant elevation in global 5-mC levels of about 2–7% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 88 publications
(96 reference statements)
1
14
0
Order By: Relevance
“…Although the lack of statistical significance in our study may be the result of the relatively low number of samples and the large number of simultaneously examined CpG sites (27,578), our results are consistent with recent findings showing no change in the overall or global (not site-specific) level of 5-methylcytosine in whole blood from HD patients using an ELISA test ( 30 ), as well as the recent study where the comparison between HD and control cortex samples failed to identify statistically significant differentially methylated regions ( 14 ). Nevertheless, while 5-mC methylation in the cortex was shown to have minimal association with HD status, the study found its level to be associated with age-of-onset ( 14 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although the lack of statistical significance in our study may be the result of the relatively low number of samples and the large number of simultaneously examined CpG sites (27,578), our results are consistent with recent findings showing no change in the overall or global (not site-specific) level of 5-methylcytosine in whole blood from HD patients using an ELISA test ( 30 ), as well as the recent study where the comparison between HD and control cortex samples failed to identify statistically significant differentially methylated regions ( 14 ). Nevertheless, while 5-mC methylation in the cortex was shown to have minimal association with HD status, the study found its level to be associated with age-of-onset ( 14 ).…”
Section: Discussionsupporting
confidence: 91%
“…Plasma homocysteine is responsible for decreased DNA methylase activity, and is an independent risk factor for AD, known to occur at disease onset ( 35 ). Similarly, global DNA methylation in blood was shown in amyotrophic lateral sclerosis ( 30 , 36 ), as well as spinocerebellar ataxias 1 and 2 ( 30 ). However, in Parkinson's disease, similarly to HD, differential DNA methylation of the alfa-synuclein gene was not confirmed in blood ( 37 ), despite being shown to be differentially methylated in brain cells of patients and healthy controls ( 38 ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The output counts were used as a score to denote the strength of the evidence for each gene with ALS in GeneRIF and DisGeNet databases (Table A2). (Hamzeiy et al, 2018).…”
Section: Gene Coexpression Network Analysismentioning
confidence: 99%
“…Recently, elevated global DNA ME was observed in SCA 1 and 2 [111]. In a SCA7 mouse model, CCCTCbinding factor (CTCF) acts as a trans-acting factor that interacts in a ME-dependent manner with the adjacent cis-environment to prevent expansion of CAG repeat [112].…”
Section: Epigenetic Factorsmentioning
confidence: 99%